2021
DOI: 10.1088/1757-899x/1140/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of AlCrN coating deposited on TiB2/Ti composites sintered by SPS dedicated for high temperature tribological applications

Abstract: The aim of the work was to investigate the adhesion of AlCrN coating deposited by PVD method on TiB2/Ti composites manufactured by Spark Plasma Sintering (SPS). The composites were produced from three kinds of mixtures of powders: (1) Ti and TiB2, (2) Ti6Al4V and TiB2 and (3) Ti and B. Each of the mixtures was prepared at 50/50 wt. % ratio of components. Before the coating deposition the specimens were polished to obtain the surface roughness typically required for machine parts. For each set of specimens an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The previous study has shown that the TiB 2 /Ti composites preparation process is the factor which determines the PVD coating adhesion, which in practice can be evaluated only in the experimental manner [24]. The present study is a continuation of the previous work and shows the AlCrN PVD coating tribological performance, from the point of view of the impact of TiB 2 /Ti composite substrate composition and manufacturing technology parameters, with a special emphasis on coating wear mechanisms at high temperatures.…”
Section: Introductionmentioning
confidence: 57%
“…The previous study has shown that the TiB 2 /Ti composites preparation process is the factor which determines the PVD coating adhesion, which in practice can be evaluated only in the experimental manner [24]. The present study is a continuation of the previous work and shows the AlCrN PVD coating tribological performance, from the point of view of the impact of TiB 2 /Ti composite substrate composition and manufacturing technology parameters, with a special emphasis on coating wear mechanisms at high temperatures.…”
Section: Introductionmentioning
confidence: 57%
“…On the basis of the previously presented results [12,13], the selection of input powder materials and methods of preparation for ceramic-based bulk TiB 2 /Ti composites, intended for high-temperature PVD coatings, was made. Samples were prepared to obtain the composite with Ti/TiB 2 , with the ratio of 15/85 wt% in a fully reacted state.…”
Section: Tib 2 /Ti Compositesmentioning
confidence: 99%
“…The average roughness (R a ) measured by a noncontact 3D profiler was 0.067 ± 0.007 µm. The details of the surface preparation procedure are provided in [13]. For composite materials, the surface preparation is much more complex as compared to steel alloys due to the presence of at least two phases with different mechanical properties and the presence of pores.…”
Section: Surface Finishingmentioning
confidence: 99%